2016
DOI: 10.14238/pi53.5.2013.245-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of length of albendazole treatment against Trichuris trichiura infection

Abstract: Background Trichuris trichiura is one of the most common soil-transmitted helminth that infects school-aged children. A single dose of albendazole has been shown to have wide variations in cure and egg reduction rates. Some studies have suggested that repeated doses of albendazole might increase its effectiveness.Objective To compare the anti-trichuriasis effect of 400 mg albendazole taken daily for five consecutive days vs. seven consecutive days.Methods A randomized open clinical trial was conducted from Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…(22) The study in Langkat district, Sumatera Utara, Indonesia found that the side effects of five and seven consecutive days albendazole administration were nausea, dizziness, dry mouth, and diarrhea. (16) Our study is useful as an evaluation of the government program for giving single-dose albendazole to eliminate the three STH infections in Indonesia. This is the first study to compare the efficacy among three consecutive days, two consecutive days and single-dose of albendazole against the three types of STH infections in Indonesia, so hopefully it can increase our knowledge of a better albendazole regimen to improve children's health.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…(22) The study in Langkat district, Sumatera Utara, Indonesia found that the side effects of five and seven consecutive days albendazole administration were nausea, dizziness, dry mouth, and diarrhea. (16) Our study is useful as an evaluation of the government program for giving single-dose albendazole to eliminate the three STH infections in Indonesia. This is the first study to compare the efficacy among three consecutive days, two consecutive days and single-dose of albendazole against the three types of STH infections in Indonesia, so hopefully it can increase our knowledge of a better albendazole regimen to improve children's health.…”
Section: Resultsmentioning
confidence: 97%
“…16Similar results study were found in Gabon that the increased efficacy was found by prolonging the duration of albendazole treatment. (12,16) The living place of T. trichiura in caecum makes this worm more resistant to the anthelmintic. 17Repeated-dose of albendazole can prolong the contact time of the drug with the parasite so that it can increases the efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…The previous studies done by Jiero et al (2015) in Medan Belawan, Pasaribu (2004) and Pasaribu (2019) in Karo Regency showed A. lumbricoides as the highest infections found [5], [7], [19]. This difference may be due to the treatment for T. trichiura infections require repeated doses of albendazole [4], [28], [29]. Although albendazole is a broad-spectrum anthelmintic drug taken orally as a single dose to control intestinal worms, the treatment for T. trichiura infections is less effective than to A. lumbricoides and hookworm infections [29].…”
Section: Discussionmentioning
confidence: 96%
“…Many species of worms have been reported to cause infection in Indonesia. Only a few were found in a wide and high prevalence distribution (11), namely Ascaris lumbricoides and Trichuris trichiura.…”
Section: Introductionmentioning
confidence: 99%
“…Four antihelminthics for treating Soil-Transmitted Helminth according to WHO are albendazole, mebendazole, levamisole and pyrantel pamoate (11). Albendazole (ALB) and Mebendazole (MBZ) are recommended for infections of Ascaris lumbricoides, Trichuris trichiura, Necator americanus and Ancylostoma duodenale (12).…”
Section: Introductionmentioning
confidence: 99%